2000
DOI: 10.21273/hortsci.35.5.914
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Visual vs. Instrumental Measurement of Color Differences in Bentgrass Turf

Abstract: This study was conducted to determine: 1) if the Minolta CR-310 Chroma Meter can detect color differences among bentgrass (Agrostis stolonifera L., A. capillaris L.) cultivars maintained as a turf; 2) how the CR-310 parameters of hue angle, lightness, and chroma compare with visual color assessments; and 3) if the CR-310 can provide consistent color measurements among evaluators. Differences were detected among cultivars with respect to hue angle, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 2 publications
(4 reference statements)
0
25
0
1
Order By: Relevance
“…Using hue angle to quantify turf color has been suggested before. Studies with perennial ryegrass and creeping bentgrass found that, in situ, hue angle measured by a ChromaMeter (Minolta Co., Ramsey, NJ) served as a consistent and effective color indicator (Thorogood et al, 1993; Landschoot and Mancino 2000). The extremely small sampling areas dictated by the ChromaMeter sensor head, however, precluded its wider application for larger plot studies.…”
Section: Resultsmentioning
confidence: 99%
“…Using hue angle to quantify turf color has been suggested before. Studies with perennial ryegrass and creeping bentgrass found that, in situ, hue angle measured by a ChromaMeter (Minolta Co., Ramsey, NJ) served as a consistent and effective color indicator (Thorogood et al, 1993; Landschoot and Mancino 2000). The extremely small sampling areas dictated by the ChromaMeter sensor head, however, precluded its wider application for larger plot studies.…”
Section: Resultsmentioning
confidence: 99%
“…Turfgrass colour was measured one day before summer harvests and five days before winter harvests using a Chroma Meter (Minolta, CR-310, Osaka, Japan), an instrument previously shown to enable quantitative assessments of turfgrass colour (Landschoot and Mancino, 2000). The meter describes colour in three coordinates: L*, lightness, from 0 (black) to 100 (white); a*, from )60 (green) to 60 (red); and b*, from )60 (blue) to 60 (yellow).…”
Section: Turfgrass Qualitymentioning
confidence: 99%
“…The meter describes colour in three coordinates: L*, lightness, from 0 (black) to 100 (white); a*, from )60 (green) to 60 (red); and b*, from )60 (blue) to 60 (yellow). As recommended by Landschoot and Mancino (2000), data used to assess turf greenness were the hue angles for the CIELAB colour space (Hamill and Camlin, 1984). At any level of lightness, the hue angle is calculated as arctangent (b*/a*) and was used to describe the colour of the turfgrass; the greater the hue angle the darker the greenness of the turfgrass.…”
Section: Turfgrass Qualitymentioning
confidence: 99%
“…Turfgrass quality was assessed by measuring turfgrass colour and tissue (clippings) N concentration of each plot. Turfgrass colour was measured prior to commencing the experiment, and then every 4 weeks, using a Chroma Meter (Minolta, CR-310, Osaka, Japan); an instrument previously shown to enable quantitative assessments of turfgrass colour (Barton and Colmer 2006;Landschoot and Mancino 2000). Each turfgrass plot was divided into eight subplots (0.56 m 2 ), which did not include turfgrass within 0.5 m of each edge, which were then further divided into nine (0.0625 m 2 ) sampling squares using a sampling grid made from tensioned rope held by rods on each side.…”
Section: Turfgrass Growth and Qualitymentioning
confidence: 99%